FINANCIAL FEASIBILITY STUDY OF IMPLEMENTING ELECTRONIC ROAD PRICING (ERP) ON AHMAD YANI STREET, MANADO - Semuel Rompis (Jurnal Infrastruktur, 2023)
The objective of this study is to evaluate the financial feasibility of the Electronic Road Pricing (ERP) scheme if applied to Ahmad Yani Road Manado. Financial feasibility is feasibility from a private point of view. The motivation for this research is, that the government is encouraging the private sector or business entities to participate in investing in infrastructure development projects including supporting infrastructure such as ERP, thus hopefully the results of this research can provoke investment enthusiasm from investors. Data collection for this study was carried out over 3 days, which are Monday, Friday and Saturday on the 8th, 12th and 13th of August 2022, respectively. The 2014 Indonesian Highway Capacity Manual (PKJI) were used for data analysis. Data collection began with a vehicle volume survey and then calculating the percentage of user who will move to other route with the implementation of ERP. This percentage was obtained by distributing questionnaires to users of the Ahmad Yani Road Manado which was the study location. Then an analysis is carried out for conditions without ERP (Without Project) and with ERP (With Project). This study shows that 48% of the 400 road user respondents choose not to use the ERP road. For a feasibility analysis from a financial point of view, with a planned life span of 10 years, it shows a Benefit Cost Ratio of 2.184 (BCR > 1) and for a Net Present Value of Rp. 320,744,453,901 (NPV > 0) and for the Internal Rate of Return of 44.54% and the Payback Period is 2 years 4 months 9 days, the construction of Electronic Road Pricing (ERP) on Ahmad Yani Road Manado is considered financially feasible.